ROBOCOP II (ROBOtic assisted versus conventional open partial nephrectomy) randomised, controlled feasibility trial: clinical trial protocol - Kowalewski, Karl-Friedrich; Sidoti Abate, Marie Angela; Neuberger, Manuel; Kirchner, Marietta; Krisam, Regina; Egen, Luisa; Haney, Caelán Max; Siegel, Fabian; Michel, Maurice Stephan; Honeck, Patrick; Nuhn, Philipp; Westhoff, Niklas Christian; et al. (BMJ open, 2021)
Introduction Randomised controlled trials comparing robotic-assisted partial nephrectomy (RAPN) and open PN (OPN) are lacking. Therefore, we aim to report the study protocol and a trial update for a randomised controlled feasibility trial comparing RAPN versus OPN for renal neoplasms. Methods and analysis The ROBOtic assisted versus conventional Open Partial nephrectomy II trial is designed as a single-centre, randomised, open-label, feasibility trial. Participation will be offered to patients with renal neoplasms and deemed feasible for both, OPN and RAPN. We aim to enrol 50 patients within 15 months using a 1:1 allocation ratio. The primary endpoint of the trial is feasibility of recruitment and will be successful if one third of eligible patients agree to participate. Secondary endpoints include perioperative results, health-related quality of life, inflammatory response as well as surgical ergonomics of the operating team. If the primary outcome, feasibility of recruitment, is successful, the secondary results of the trial will be used for planning a confirmative phase III trial. Ethics and dissemination Ethical approval was obtained from the local institutional review board (Ethik-Kommission II at Heidelberg University: 2020-542N). Results will be made publicly available in peer-reviewed scientific journals and presented at appropriate congresses and social media.
Online issue publication November 03, 2021
Gesehen am 22.12.2021